The tensions between facts and fantasy - Anderson, Douglas (Studium, 2016)
Essay Review of: Laura Snyder, Eye of the Beholder: Johannes Vermeer, Antoni van Leeuwenhoek, and the Reinvention of Seeing (New York: W. W. Norton 2015) ISBN 0393077462, 448 pp, ill., 27.95.